PENGEMBANGAN LKPD BERBASIS HIGHER ORDER THINKING SKILL (HOTS) PESERTA DIDIK KELAS XI SMA YP PGRI 2 MAKASSAR PADA MATERI GENETIKA - Sri Mukminati Nur (Jurnal Biogenerasi, 2022)
Online and offline learning emerged as a form of learning pattern in the era of information technology as it is today. Based on the results of interviews conducted with Biology teachers at SMA YP PGRI 2 Makassar, the researchers obtained the following constraints and impacts: (1) the learning media used by the teachers was dominantly monotonous and made students feel bored or bored, (2) the dominant learning was not interactive. so that students are lazy to do assignments or read teaching materials, (3) too many assignments are given without clear working instructions so that the subject matter is difficult to understand, (4) lack of mastery of technology including the available platforms as a result the teacher does not use technology properly. From the above background, researchers conducted a study to determine the validity and practicality of developing LKPD based on Higher Order Thinking Skill (HOTS) for class XI students at SMA YP PGRI 2 Makassar. The type of research used is ADDIE Model development research which consists of five steps, namely: (1) analysis (analyze), (2) design, (3) development, (4) implementation, ( 5) evaluation (evaluation). The research instrument used response questionnaires, learning outcomes tests and validation sheets. The results showed that the LKPD based on Higher Order Thinking Skill (HOTS) on genetic material was valid and practical.